PERFORMANSI WLAN KANTOR PUSAT PEMERINTAH KABUPATEN BADUNFG - Linawati, Linawati; Gunantara, Nyoman; Gunawan, I K. A. Riki (Jurnal Teknologi Elektro; Vol 14 No 2 (2015): (July - December) Majalah Ilmiah Teknologi Elektro, 2016)
WLAN has been implemented widely, including in public area and government office. Badung Regency office has got benefit from the technology in applying its e- government services. However the WLAN performance in term of its QoS has not been evaluated after its installation. Then its delay, packet loss, throughput, and jitter were measured using Ekahau Heatmapper, Axence Nettols, Wi-Fi Analyzer , and Ubiquiti Unifi. The WLAN coverage area was calculated and analyzed. Generally, the performance is good. However there are areas in all 12 buildings in the offices that are needed more access points.
Keywords: WLAN